1977
DOI: 10.1080/16070658.1977.11689043
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Effects on Microwave-SncHiced Hyperthermia and Neurochemical Correlates

Abstract: This paper describes the effect of field orientation on the hyperthermia produced by microwave irradiation. Rats exposed in the E-orientation (long-axis of animal parallel to E-field) to 1600 tmhz radiation become significantly hotter than those exposed in the H-field at the same power density. Norepinephrine and dopamine, but not serotonin content of the basal hypothalamus is reduced as a concomitant of microwave-induced brain hyperthermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1983
1983
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Yuan et al (1989) found that in mice, the exposure to 45 8C for 15 min reduced the brain content of norepinepherine (NE) and serotonin (5-HT). Moreover, the NE and dopamine contents in the basal hypothalamus were found by Merritt et al (1977) to be reduced as a concomitant of microwave-induced brain hyperthermia. Bliss et al (1968) and Abdel Hamid et al (1994) reported that, a variety of acute stresses (food, shock, cold, anoxia, aggregation and radiation) caused a decrease in level of norepinepherine in brains of mice, rats, guinea pigs, dogs, rabbits and monkeys.…”
Section: The Monoamines Concentration Changesmentioning
confidence: 95%
“…Yuan et al (1989) found that in mice, the exposure to 45 8C for 15 min reduced the brain content of norepinepherine (NE) and serotonin (5-HT). Moreover, the NE and dopamine contents in the basal hypothalamus were found by Merritt et al (1977) to be reduced as a concomitant of microwave-induced brain hyperthermia. Bliss et al (1968) and Abdel Hamid et al (1994) reported that, a variety of acute stresses (food, shock, cold, anoxia, aggregation and radiation) caused a decrease in level of norepinepherine in brains of mice, rats, guinea pigs, dogs, rabbits and monkeys.…”
Section: The Monoamines Concentration Changesmentioning
confidence: 95%
“…In contrast, a decrease in the hypothalamic norepinephrine concentration was reported in rats submitted to microwave induced brain hyperthermia [Merritt et al, 1977]. The serotonergic system of the brain plays an important facilitating role in the regulation of heat dissipation, whereas the noradrenergic system counteracts the serotonergic system and, therefore, enhances heat production (for review see [Brück and Hinckel, 1990]).…”
Section: Effects On Neurotransmitter Systemsmentioning
confidence: 96%
“…An increase in the cortical and hypothalamic concentrations of serotonin and 5-hydroxyindoleacetic acid has been described following acute exposure of rats to continuous microwaves at power densities of 5-10 W/cm 2 [Inaba et al, 1992]. In contrast, a decrease in the hypothalamic norepinephrine concentration was reported in rats submitted to microwave induced brain hyperthermia [Merritt et al, 1977]. The serotonergic system of the brain plays an important facilitating role in the regulation of heat dissipation, whereas the noradrenergic system counteracts the serotonergic system and, therefore, enhances heat production (for review see [Brück and Hinckel, 1990]).…”
Section: Effects On Neurotransmitter Systemsmentioning
confidence: 99%
“…In aseparate study, Merritt et al (1977) observed a decrease in rat hypothalamic norepinephrine and dopamine after a lO-min whole-body exposure to 1.6-GHz microwaves at 20mW/cm 2 (est. SAR 6.0W/kg) but not at 10mW/cm 2 • The former power density was associated with increased temperature, while the latter was not.…”
Section: Brain Chemistrymentioning
confidence: 96%